2023
DOI: 10.1088/1361-6382/acc0c6
|View full text |Cite
|
Sign up to set email alerts
|

Late-time post-merger modeling of a compact binary: effects of relativity, r-process heating, and treatment of transport

Abstract: Detectable electromagnetic counterparts to gravitational waves from compact binary mergers can be produced by outflows from the black hole-accretion disk remnant during the first ten seconds after the merger. Two-dimensional axisymmetric simulations with effective viscosity remain an efficient and informative way to model this late-time post-merger evolution. In addition to the inherent approximations of axisymmetry and modeling turbulent angular momentum transport by a viscosity, previous simulations often … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…We find no evidence for late fallback accretion, as all models exhibit a smooth power-law decline in the mass accretion rate (Figure 1(a)). However, in the absence of neutrino cooling, heavy nuclei, and radioactive heating (e.g., Desai et al 2019;Haddadi et al 2023), we cannot preclude a definitive conclusion regarding late-time fallback of the tail. In a recent study, Metzger & Fernández (2021) found that the marginally bound tail progressively falls back into the disk, but it quickly becomes unbound due to its inability to efficiently cool down.…”
Section: Sub-and Mildly Relativistic Outflowsmentioning
confidence: 91%
See 1 more Smart Citation
“…We find no evidence for late fallback accretion, as all models exhibit a smooth power-law decline in the mass accretion rate (Figure 1(a)). However, in the absence of neutrino cooling, heavy nuclei, and radioactive heating (e.g., Desai et al 2019;Haddadi et al 2023), we cannot preclude a definitive conclusion regarding late-time fallback of the tail. In a recent study, Metzger & Fernández (2021) found that the marginally bound tail progressively falls back into the disk, but it quickly becomes unbound due to its inability to efficiently cool down.…”
Section: Sub-and Mildly Relativistic Outflowsmentioning
confidence: 91%
“…However, this necessarily requires the jet launching to be longer than a typical sGRB duration of 1 s. We stress that the exclusion of the alpha recombination effect in our simulations is unlikely to impact this conflict. The reason is that these factors only start to influence the mass accretion rate after the neutrino luminosity decreases at t ∼ 0.5 s, shifting the accretion rate from  ~-M t 2 to t 3 (Haddadi et al 2023). As a result, their impact on the jet luminosity is negligible within the typical duration of sGRBs, t  1 s.…”
Section: Jet Launchingmentioning
confidence: 99%
“…MHD disk models typically drive an early, fast outflow powered by heat and magnetic forces (Siegel & Metzger 2017;Christie et al 2019) and a late, slow outflow powered by turbulent viscosity (Shakura & Sunyaev 1973). The latter outflow is enhanced by nuclear recombination incorporated into the nuclear statistical equilibrium finite temperature equation of state (Fernández et al 2019;Fahlman & Fernández 2022;Just et al 2022;Haddadi et al 2023). Our disk is no exception, and the more massive late-time outflow is from the slower viscous mechanism.…”
Section: From Tracer To Trajectorymentioning
confidence: 90%
“…If the disrupted NS has a purely toroidal field configuration, Φ is not constant but slowly increases due to the dynamo process.11 The postmerger disk mass is negligible compared to the BH mass, so no appreciable spin-down is expected in binary mergers.12 More massive BHs generally only lead to more compact disks (e.g.,Fernández et al 2020), making this result robust.13 Energy injection from alpha-particle recombination can also act to steepen the mass accretion power law after neutrino cooling is no longer important at t  1 s(Metzger et al 2008a;Haddadi et al 2023). …”
mentioning
confidence: 88%